Phylogeographic Analyses Reveal the Early Expansion and Frequent Bidirectional Cross-Border Transmissions of Non-pandemic HIV-1 Subtype B Strains in Hispaniola - Bello, Gonzalo; Arantes, Ighor; Lacoste, Vincent; Ouka, Marlene; Boncy, Jacques; Césaire, Raymond; Liautaud, Bernard; Nacher, Mathieu; Dos Santos, Georges (Frontiers in Microbiology, 2019)
The HIV-1 subtype B probably circulates in the island of Hispaniola since the 1960s; but information about the early viral history in this Caribbean island is scarce. In this study, we reconstruct the dynamics of dissemination of early divergent non-pandemic subtype B lineages (designated BCAR) in Hispaniola. To this end, we analyzed 127 HIV-1 subtype B pol sequences collected in Haiti between 2009 and 2014, combined with BCAR pol sequences from Haiti (n = 12) and the Dominican Republic (n = 123) previously described. Phylogenetic analyses supported that BCAR strains account for most (>70%) of HIV-1 subtype B infections in Haiti. The BCAR strains from Haiti and the Dominican Republic were highly intermixed among each other, although the null hypothesis of completely random mixing was rejected. Bayesian phylogeographic analyses placed the ancestral BCAR virus in Haiti and the Dominican Republic with the same posterior probability support (0.50). These analyses estimate frequent viral transmissions between Haiti and the Dominican Republic since the early 1970s onwards and the presence of local BCAR transmission networks in both countries before first AIDS cases were officially recognized. Demographic reconstructions point that the BCAR epidemic in Hispaniola growth exponentially (with a median growth rate of 0.50 year-1) until the late 1990s, after which the effective population size started to decline. These findings support that the HIV-1 epidemics in Haiti and the Dominican Republic have been connected by a recurrent bidirectional viral flux since the initial phase, which poses a great challenge for tracing the spatial root of the BCAR epidemic within Hispaniola using only genetic data. These data also reinforce the notion that prevention programs have successfully reduced the rate of new HIV-1 transmissions in Hispaniola since the end of 1990s and are likely to benefit from the implementation of integrative bi-national initiatives